Principles of Myroslav Skoryk’s Individual Style of Music in the Piano Cycle of Preludes and Fugues - Liutsiia Tsiganiuk (Edukacja Muzyczna, 2021)
The article is devoted to the works of Myroslav Skoryk, a prominent Ukrainian composer, who is well known on the Polish music scene. Two pairs of preludes and fugues from the polyphonic cycle for piano are discussed in particular: C major No. 1 and F major No. 6. The compositions are subjected to musicological and performance analysis. The stylistic and interpretative specificity of these pieces is also considered.